Clinical impact of Pseudomonas aeruginosa colonization in patients with Primary Ciliary Dyskinesia. (October 2017) - Cohen-Cymberknoh, Malena; Weigert, Nir; Gileles-Hillel, Alex; Breuer, Oded; Simanovsky, Natalia; Boon, Mieke; De Boeck, Kris; Barbato, Angelo; Snijders, Deborah; Collura, Mirella; Pradal, Ugo; Blau, Hannah; et al.
Abstract: Background: Airway infections in Primary Ciliary Dyskinesia (PCD) are caused by different microorganisms, including pseudomonas aeruginosa (PA). The aim of this study was to investigate the association of PA colonization and the progression of lung disease in PCD. Methods: Data from 11PCD centers were retrospectively collected from 2008 to 2013. Patients were considered colonized if PA grew on at least two separate sputum cultures; otherwise, they were classified as non-colonized . These two groups were compared on the lung function computed tomography (CT) Brody score and other clinical parameters. Results: Data were available from 217 patients; 60 (27.6%) of whom were assigned to the colonized group. Patients colonized with PA were older and were diagnosed at a later age. Baseline forced expiratory volume at 1 s (FEV1 ) was lower in the colonized group (72.4 ± 22.0 vs. 80.1 ± 18.9, % predicted, p = 0.015), but FEV1 declined throughout the study period was similar in both groups. The colonized group had significantly worse CT-Brody scores (36.07 ± 24.38 vs. 25.56 ± 24.2, p = 0.034). A subgroup analysis with more stringent definitions of colonization revealed similar results. Conclusions: Lung PA colonization in PCD is associated with more severe disease as shown by the FEV1 and CT score. However, the magnitude of decline in pulmonary function was similar in colonized and non-colonized PCD patients. Highlights: The rate of pseudomonas colonization in PCD is about 25–30%. Pseudomonas colonization in PCD is associated with worse lung function and CT score. Pseudomonas colonization risk increases with age and with delayed PCD diagnosis.